Functional outcome after traumatic cervical spinal cord injury is superior in adolescents compared to adults. (March 2019) - Geuther, Martina; Grassner, Lukas; Mach, Orpheus; Klein, Barbara; Högel, Florian; Voth, Maika; Bühren, Volker; Maier, Doris; Abel, Rainer; Weidner, Norbert; Rupp, Rüdiger; Fürstenberg, Carl Hans; et al.
Abstract: Objective: Determining differences in neurological and functional outcome between adolescents and adults after acute traumatic spinal cord injury (SCI). Design: Retrospective, multi-center case–control study. Methods: 100 cases of patients under 18 years at accident with acute traumatic cervical SCI admitted to SCI centers participating in the European Multi-center study about SCI (EMSCI) between January 2005 and April 2016 were reviewed. According to their age at accident, age 13 to 17, patients were selected for the adolescent group. After applying in- and exclusion criteria 32 adolescents were included. Each adolescent patient was matched with two adult SCI patients for analysis. Outcome measures: ASIA Impairment scale (AIS) grade, neurological, sensory, motor level, total motor score, and Spinal Cord Independence Measure (SCIM III) total score. Results: Mean AIS conversion, neurological, motor and sensory levels as well as total motor score showed no significantly statistical difference in adolescents compared to the adult control group after follow up of 6 months. Significantly higher final SCIM scores (p < 0.05) in the adolescent group compared to adults as well as a strong trend for a higher gain in SCIM score (p < 0.061) between first and last follow up was found. Conclusions: Neurological outcome after traumatic cervical SCI is not superior in adolescents compared to adults in this cohort. Significantly higher SCIM scores indicate more functional gain for the adolescent patients after traumatic cervical SCI. Juvenile age appears to be an independent predictor for a better functional outcome. Highlights: Neurological outcome after traumatic cervical SCI is not superior in adolescents compared to adults. Adolescent patients have more functional gain after traumatic cervical SCI. Juvenile age appears to be an independent predictor for a better functional outcome after traumatic cervical SCI.